PREVENT HEART DISEASE FROM AN EARLY STAGE: EDUCATION ON THE USE OF ANTIHYPERTENSIVE MEDICATION AND HEALTHY LIFESTYLE PRACTICES - Nadiya Nurul Afifah; Reinaldo Pradama; Siaw Yi Ping; Fadhila Auliya Putri (Abdi Dosen : Jurnal Pengabdian Pada Masyarakat, 2026)
Hypertension is a major risk factor for cardiovascular disease, with a prevalence that continues to increase. Efforts to control hypertension do not rely solely on pharmacological therapy but also require improved public knowledge and behavioral changes. This community service activity aimed to evaluate blood pressure profiles and community knowledge levels before and after educational interventions regarding the use of antihypertensive medications and healthy lifestyle practices. The method involved health education sessions accompanied by blood pressure measurements and assessment of knowledge levels using questionnaires. The results showed variations in participants’ blood pressure, with 31% remaining in the hypertensive category. In addition, participants’ knowledge scores increased by 54% after the educational intervention. This activity is expected to enhance community awareness and understanding of hypertension prevention and control in Block A.8, Jl. Perumahan Kebon Jeruk Baru No. 29 Block A3, RT 5/RW 8, Kebon Jeruk District, West Jakarta, Indonesia.